Pengembangan Modul Pelatihan dan Bahan Konseling bagi Konselor Sebaya Remaja di Sekolah Menengah - Lailatul Fitriyah; Faizatul Munawwaroh; Lailatur Rohmah; Liza Umami; Nada Fitriyah (CV. ITTC INDONESIA, 2023)
Counseling in secondary schools plays a crucial role in providing psychosocial support and services for adolescents. However, in many schools in remote areas, the implementation of counseling faces various challenges, resulting in suboptimal counseling services. This research aims to develop a training module and counseling materials suitable for peer counselors in secondary schools. Preliminary studies indicate issues in counseling implementation, especially in remote areas, where counselors often lack a counseling education background. This limitation hinders effective counseling services for students in need. The research adopts a qualitative approach with the research and development (R&D) method. Data is collected through interviews, observations, and questionnaires from peer counselors, students, teachers, and other relevant stakeholders. The research stages include needs analysis, module design, development, limited trials, evaluation, revision, implementation, and effectiveness evaluation. The research results in a structured training module and counseling materials in the form of reading texts and PowerPoint presentations. These materials are designed to enhance the knowledge and skills of peer counselors in conducting effective counseling. The implementation of the module and counseling materials in secondary schools shows positive responses from peer counselors and students. Findings from effectiveness evaluations indicate that the training module and counseling materials positively contribute to improving peer counselors' understanding of counseling and assisting students in overcoming adolescent problems and challenges. Therefore, the development of these training modules and counseling materials is expected to serve as a useful guide and resource for peer counselors in secondary schools, particularly in remote areas, to enhance the quality of counseling services and ensure effective support for students.